2018
DOI: 10.1111/hae.13444
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Medtep Hemophilia online platform for adherence to prophylactic treatment in haemophilia patients: Results from a 1‐year observational study

Abstract: The Medtep Hemophilia online platform helped the studied patients with haemophilia to improve their adherence to prophylactic treatment, while increasing their QoL and illness perception, as well as joint arthropathies stabilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 37 publications
2
20
0
1
Order By: Relevance
“…This resulted in increased patient quality of life (QoL) and enhanced illness perception and stabilization of joint health after 1 year. 19 In concordance with previous studies, PWH in our sample also reported that iCHIP Both people with severe and with non-severe haemophilia in our sample found it useful to use visuals in their interaction with the Team. Indeed, a good relationship between care providers and PWH has been found to be associated with treatment adherence in haemophilia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This resulted in increased patient quality of life (QoL) and enhanced illness perception and stabilization of joint health after 1 year. 19 In concordance with previous studies, PWH in our sample also reported that iCHIP Both people with severe and with non-severe haemophilia in our sample found it useful to use visuals in their interaction with the Team. Indeed, a good relationship between care providers and PWH has been found to be associated with treatment adherence in haemophilia.…”
Section: Discussionsupporting
confidence: 92%
“…9 Our results, based on the perspectives of patients, suggest that visualization techniques could be a helpful patient-centred care strategy. 17,18 In another study, 19 Several decision aids have been developed for haemophilia. A previous qualitative study demonstrated that a better understanding determines the ability to practice prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Some experiences of the implementation of electronic devices replacing the paper registries have been presented in international congresses . In a recent study, the use of an app improved the adherence measured with the VERITAS‐Pro scale, quality of life and illness perception after 1 year . Several experiences of telehealth in haemophilia have been reported, including an interesting experience of telemedicine by videoconference in paediatric patients .…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21] In a recent study, the use of an app improved the adherence measured with the VERITAS-Pro scale, quality of life and illness perception after 1 year. 22 Several experiences of telehealth in haemophilia have been reported, 23 including an interesting experience of telemedicine by videoconference in paediatric patients. 24 The results of our survey highlight the preference for apps, and we are implementing the employment of a specific app for recording infusions and bleed-related occurrences.…”
Section: Pro Scale (Validated Haemophilia Regimen Treatment Adherencementioning
confidence: 99%
“…Formal evaluation of the Be Involved services, specifically the home care infusion component is integral to making effectual program adjustments. Currently, most haemophilia care research focusses on self‐management, transitional care programs and adherence outcomes, particularly in adolescents . For example, one study addressing home care infusion services as part of the collective ‘Haemophilia Community’ looked at men's perceptions of management through a resilience framework .…”
Section: Introductionmentioning
confidence: 99%